Blinatumomab as postremission therapy replaces consolidation and substantial parts of maintenance chemotherapy and results in stable MRD negativity in children with newly diagnosed B-lineage ALL - Guenter Henze; Ekaterina Mikhailova; Alexander Popov; Julia Roumiantseva; Oleg Budanov; Svetlana Lagoyko; Liudmila Zharikova; Natalia Miakova; Dmitry Litvinov; Lili Khachatryan; Alexey Pshonkin; Natalia Ponomareva; et al. (Journal for ImmunoTherapy of Cancer)
The bispecific T cell-binding antibody blinatumomab (CD19/CD3) is widely and successfully used for the treatment of children with relapsed or refractory B-cell precursor acute lymphoblastic leukemia (BCP-ALL). Here, we report the efficacy of a single course of blinatumomab instead of consolidation chemotherapy to eliminate minimal residual disease (MRD) and maintain stable MRD-negativity in children with primary BCP-ALL.Between February 2020 and November 2022, 177 children with non-high-risk BCP-ALL were enrolled in the ALL-MB 2019 pilot study (NCT04723342). Patients received the usual risk-adapted induction therapy according to the ALL-MB 2015 protocol. Those who achieved a complete remission at the end of induction (EOI) received treatment with blinatumomab immediately after induction at a dose of 5 μg/m2/day for 7 days and 21 days at a dose of 15 μg/m2/day, followed by 12 months of maintenance therapy. MRD was measured using multicolor flow cytometry (MFC) at the EOI, then immediately after blinatumomab treatment, and then four times during maintenance therapy at 3-month intervals.All 177 patients successfully completed induction therapy and achieved a complete hematological remission. In 174 of these, MFC-MRD was measured at the EOI. 143 patients (82.2%) were MFC-MRD negative and the remaining 31 patients had varying degrees of MFC-MRD positivity.MFC-MRD was assessed in all 176 patients who completed the blinatumomab course. With one exception, all patients achieved MFC-MRD negativity after blinatumomab, regardless of the MFC-MRD score at EOI. One adolescent girl with high MFC-MRD positivity at EOI remained MFC-MRD positive. Of 175 patients who had completed 6 months of maintenance therapy, MFC-MRD data were available for 156 children. Of these, 155 (99.4%) were MFC-MRD negative. Only one boy with t(12;21) (p13;q22)/ETV6::RUNX1 became MFC-MRD positive again. The remaining 174 children had completed the entire therapy. MFC-MRD was examined in 154 of them, and 153 were MFC-MRD negative. A girl with hypodiploid BCP-ALL showed a reappearance of MFC-MRD with subsequent relapse.In summary, a single 28-day course of blinatumomab immediately after induction, followed by 12 months of maintenance therapy, is highly effective in achieving MRD-negativity in children with newly diagnosed non-high risk BCP-ALL and maintaining MRD-negative remission at least during the treatment period.